Effects of hormone therapy and tibolone on body composition and serum leptin levels in postmenopausal women - (:unkn) unknown (ELSEVIER SCIENCE INC, 2009)
Objective: To compare the changes in body composition and in leptin levels in postmenopausal women receiving hormone therapy (HT) or tibolone. Design: Prospective comparative study. Setting: Menopause Unit in a tertiary Hospital. Patient(s): One hundred twenty women were recruited. Intervention(s): Women were assigned into a control group, HT, and tibolone group. Main Outcome Measure(s): Anthropometric indices., leptin levels, tissue fat percentage, total fat, and lean mass measurements were performed at baseline and after 6 months. Result(s): The serum leptin levels were in strong correlation with the total fat percentage and total fat mass at baseline. Untreated women had weight gain and a gradual decrease in leptin levels. Women receiving HT had significantly increased leptin levels. Women in the tibolone group, however, had a significant decrease in leptin levels accompanied by decreased total fat mass, fat percentage, and increased total lean mass. The changes in leptin levels were more pronounced in lean women. Conclusion(s): Postmenopausal women tend to gain weight accompanied with a reduction in leptin concentrations. Hormone therapy administration increases leptin levels while maintaining body weight and body fat distribution, whereas tibolone use decreases leptin levels, total fat percentage, and total fat mass. (Fertil Steril (R) 2009;91:425-31. (C)2009 by American Society for Reproductive Medicine.)
Keywords: Hormone therapy; tibolone; leptin; body composition; REPLACEMENT THERAPY; PLASMA LEPTIN; GENDER-DIFFERENCES; TRANSDERMAL ESTRADIOL; SEXUAL-DIMORPHISM; FAT DISTRIBUTION; ADIPOSE-TISSUE; OBESE GENE; IN-VITRO; WEIGHT